Examining Islamic Spiritual Motives on Online Transportation Business: The Case of Millennial Generation - Mochlasin, Mochlasin; Puspita, Rosana Eri; Abdul Hamid, Nor 'Adha Binti (IKONOMIKA, 2023)
The transportation sector has contributed significantly to economic activities, especially after the development of digital technology. In the online transportation business, customer satisfaction is determined not only by the functional benefit factor but also by another role often overlooked by actors, namely emotional benefits in the form of spiritual motives. This research aims to analyze the influence of customer value on millennial customer satisfaction and the role of spiritual motives in the influence of customer value on millennial customer satisfaction. This study uses a quantitative approach with a population of all millennial customers on Go-Jek online transportation. Sampling used the convenience sampling method involving 250 millennial customers who live in the Special Province of Yogyakarta, Indonesia. The analysis used in this study is an analysis of variance to test the proposed hypothesis. The results showed that customer value affects customer satisfaction. In addition, the spiritual motive variable strengthens the influence of the customer value variable on customer satisfaction. The study's results recommend that to maintain customer loyalty, one should consider the factors that cause customer satisfaction: technology acceptance, trust, lifestyle, service ethics, and spiritual motives.